The Distribution of Inheritance Rights To Heirs of Different Religions: Study of Court Decision Number 0554/PDT.P/2023/PA.SBY - Icha Choerunnisa; Tjempaka, Tjempaka (Dinasti Research, 2024)
In Indonesia's multicultural society, inheritance issues frequently arise where family members may hold different religious beliefs. These differences often trigger social issues, including inheritance disputes that require legal handling. Indonesia, predominantly Muslim, has regulations such as the Compilation of Islamic Law that govern inheritance. Inheritance issues are particularly complex in cases of interfaith marriages. In the Compilation of Islamic Law, religious differences can pose barriers to inheritance, according to the majority of scholars. However, courts have adapted, based on jurisprudence No. 51K/AG/1999, regarding compulsory wills, allowing non-Muslim heirs to receive inheritance rights. The research focuses on Decision Number 0554/Pdt.P/2023/PA.Sby, which addresses a multicultural inheritance dispute, reflecting challenges in applying Islamic inheritance law in a multireligious context. This highlights the need for flexible and empathetic interpretation of the law to achieve social justice. This study employs a normative juridical method and finds that the analysis of Court Decision Number 0554/Pdt.P/2023/PA.Sby reveals that although Islamic law prohibits heirs of different religions from inheriting, courts can use ijtihad (independent reasoning) and consider fairness and societal values. In this context, compulsory wills can be a solution to grant inheritance to non-Muslim heirs. This decision reflects the legal flexibility in addressing religious diversity in Indonesia and underscores the importance of protecting the rights of heirs fairly.